Knowledge, Attitude, Behavior and Myth towards Epilepsy among Community People - Gupta, Bimala Shah; Laxmi, BK (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Epilepsy represents one of the major brain disorders worldwide. Living in the society is more challenging than epilepsy itself. The main objective of the study was to find out knowledge, attitude, behavior and myth towards epilepsy among community people. Methods: The descriptive cross-sectional study design was adopted with the systematic random sampling. A structured, pretested interview questionnaire was used to collect data and analyzed by using descriptive statistics. Results: Of the 50 respondents. With regards to knowledge, attitude, behavior and myth towards epilepsy, 100% correctly thought that epilepsy is a brain disorder while 70% believed it to be a psychiatric disorder and an inherited disorder (70%). Most of them thought that epilepsy can be cured (90%). Similarly 94% viewed that a person with epilepsy takes up a job. About 78% of the respondents would throw the water on the person and 50% would make the person smell a shoe during seizure. Similarly 14% would take the person to the Dhami/Jhankri. Myths found to be prevalent were epilepsy is transmitted by eating non vegetarian diet (18%), caused by an evil/supernatural power (26%) and can be treated by spiritual healer (18%). Conclusions: Although majority of the respondents had heard of epilepsy. False attitude, behavior and myth about the condition still prevail in a community. It may be worthwhile including awareness programs about epilepsy by community education/ local health organization in order to dispel the false attitude, behavior and manage the person with epilepsy in community as well.